In Vitro Study of Synergic Effect of Cisplatin and Low Molecular Weight Heparin on Oral Squamous Cell Carcinoma - Camacho-Alonso, Fabio; Gómez-Albentosa, T.; Oñate-Sánchez, R. E.; Tudela-Mulero, M. R.; Sánchez-Siles, M.; Gómez-García, Francisco J.; Guerrero-Sánchez, Yolanda (Frontiers in Oncology, 2020)
Objectives: To evaluate the possible synergic effect of cisplatin and low molecular weight heparin (LMWH) on oral squamous cell carcinoma (OSCC). Materials and Methods: Cisplatin and enoxaparin sodium, alone or in combination, were administered at doses of 1, 2, 4, 8 and 10 µM and 0.1, 0.5, 1, 5, 10, 50 and 100 µg/mL respectively to the H357 human OSCC line. The effects on cell viability and apoptosis were evaluated after 24, 48 and 72 hours and on cell migration after 18 and 24 hours. Results: 10 µM concentration of cisplatin produced the greatest decrease in cell viability, with significant differences at 24 (p=0.009), 48 (p=0.001) and 72 hours (p=0.003); the 100 µg/mL dose of enoxaparin produced the greatest decrease in cell viability but without significant differences (p>0.05). When different concentrations of cisplatin and enoxaparin were combined, it was found that 100 µg/mL enoxaparin sodium produced the greatest synergic effect on cell viability reduction. In analyses of apoptosis and cell migration, it was found that the combination of cisplatin at 8 or 10 μM and 100 μg/ml enoxaparin produced a higher rate of apoptosis at 24, 48 and 72 hours and a greater reduction in cell migration at 18 and 24 hours. Conclusions: A combination of cisplatin and enoxaparin sodium shows a synergic effect that reduces cell viability and cell migration capacity and increases the apoptosis of human OSCC cells. Clinical relevance: Enoxaparin may be beneficial in chemotherapy for patients with OSCC; this finding requires further clinical and laboratory investigation.